2023
DOI: 10.1097/hcr.0000000000000826
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Socioeconomic Status Patients Have Extremely High-Risk Factor Profiles on Entry to Cardiac Rehabilitation

Sherrie Khadanga,
Patrick D. Savage,
Philip A. Ades
et al.

Abstract: Purpose: Patients with lower socioeconomic status (SES) have higher rates of cardiovascular events, yet are less likely to engage in secondary prevention such as cardiac rehabilitation (CR). Given the low number of lower-SES patients entering CR, characterization of this population has been difficult. Our CR program specifically increased recruitment of lower-SES patients, allowing for careful comparison of medical, psychosocial, and behavioral risk factors between lower- and higher-SES patients el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This sample was a population at higher risk for complications, as generally seen in patients with lower SES. 5 More than 40% were smoking at the time of diagnosis (a subgroup for which attendance is particularly difficult), 52,53 CRF levels were exceptionally low, and many had concerning scores on depression or cognitive functioning. Additionally, during the trial, 315 ED visits, 126 hospitalizations, and 10 deaths also occurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sample was a population at higher risk for complications, as generally seen in patients with lower SES. 5 More than 40% were smoking at the time of diagnosis (a subgroup for which attendance is particularly difficult), 52,53 CRF levels were exceptionally low, and many had concerning scores on depression or cognitive functioning. Additionally, during the trial, 315 ED visits, 126 hospitalizations, and 10 deaths also occurred.…”
Section: Discussionmentioning
confidence: 99%
“…However, disparities by SES are largely due to modifiable behaviors . Patients with lower SES have higher-risk cardiac profiles (smoking, obesity, diabetes, and lower cardiorespiratory fitness [CRF]), which result in increased rates of cardiac events . Thus, the increased morbidity and mortality following a cardiac event in individuals with lower SES may be modifiable by engaging in cardiac rehabilitation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their findings, Khadanga and colleagues propose the incorporation of more patient-centric interventions within standard CR programs aimed to specifically address the disparate CVD risk factor profiles noted in their study 11. For example, they suggest implementing referrals to interventions for psychological symptom treatment and incorporating behavioral weight loss programs with comprehensive diet and exercise education.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Despite its clear evidence base for reducing CVD and all-cause mortality, it is highly underutilized by populations experiencing socioeconomic disadvantage 10. In this issue of the Journal of Cardiopulmonary Rehabilitation and Prevention , Khadanga and colleagues provide a prospective cohort analysis examining differences in risk factor profiles among >3000 patients enrolling in outpatient phase 2 CR based on SES 11. Utilizing enrollment in Medicaid as a marker of low SES, the authors found striking differences in risk factor profiles between patients enrolled in Medicaid and those enrolled in Medicare or private insurance.…”
mentioning
confidence: 99%